Membangun Daya Saing Institusi Pendidikan Berbasis Kompetensi Dasar Organisasi - Edy Suandi Hamid (Unisia, 2008)
This article is intended to oversee some experiences of the Islamic University of Indonesia (Universitas Islam Indonesia abbreviated by UII) in developing its core competences as the main source of competetiveness to face higher education changes and challenges. As the first Islamic and national university in Indonesia, UII faces the fact that developing high quality in academic atmosphere and services to all stakeholders is no longer gained merely by its famous name as the oldest university in the country. As many universities especially state and government-funded universities and higher education institutions grow faster, UII has realised that to be a noticed part and important contributor in higher education in Indonesia, extra efforts must be accomplished. And UII started it by defining its core compteneces in several areas of educational services.As this article finds, UII has developed its core competence mainly in the arts of management and government of university. UII introduced a more simple highest level management in all units to reduce cost of activities and to fasten decision making proccess. More simple management introduced by UII has transformed it to be smaller and slimmer in structure but with more flexibility in implementing its policy. The new simple management has became one of the most interested issues by many other higher education institutions. Using this simple management, UII has developed its main activities based on its mission to promote Islamic values as blessing for all creatures.Concluding from the empirical findings obtained in the field, this article suggests several important points to universities, especially islamic ones, to develop their core competence based on management and government issues. Firstly, highest level management of university needs to take a deep look at the real world challenges faced by university that required several adjustment in internal body of university. Secondly, as changes in internal structure of university are accepted, unlimited commitment by stakeholders and higher management in a university must be taken into account and becomes the main power of internal changes. And thirdly, as Islamic values become important part of Islamic education institutions, their implementation requires more consideration by all university stakeholders.